Lecture Summaries 2002-2003 - Rodger, Richard; Pearson, Michael Parker; Campbell, Ewan (Proceedings of the Society of Antiquaries of Scotland, 2004)
Three lecture summaries: The making of classical Edinburgh Bodies under the floor: prehistoric roundhouse life at Cladh Hallan, South Uist New work on the origins of the Scots of Dál Riata